2016
DOI: 10.1021/acscatal.6b01393
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanical Screening of Single-Atom Bimetallic Alloys for the Selective Reduction of CO2 to C1 Hydrocarbons

Abstract: Electrocatalytic reduction of CO 2 to energy-rich hydrocarbons such as alkanes, alkenes, and alcohols is a very challenging task. So far, only copper has proven to be capable of such a conversion. We report density functional theory (DFT) calculations combined with the Poisson−Boltzmann implicit solvation model to show that single-atom alloys (SAAs) are promising electrocatalysts for CO 2 reduction to C 1 hydrocarbons in aqueous solution. The majority component of the SAAs studied is either gold or silver, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
171
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(176 citation statements)
references
References 72 publications
4
171
1
Order By: Relevance
“…[57] This study validated the CO* adsorption energy to be ag ood descriptor for the charget ransfer of intermediate products and discounts the volcanop lot relationship thati s widely used as ag uideline for tuning catalysts electivity.H ead-Gordon,B ell, and co-workers calculated single atoms (Cu, Ni, Pt, Pd, Cu, Rh, and Ir) added to gold and silver to converge on alloys containing Co, Rh, and Ir as particularly promisingc andidates for experimental verification. [58] 4.1. Compositional survey…”
Section: Co 2 !C 2 With Electrocatalytic Alloysmentioning
confidence: 99%
“…[57] This study validated the CO* adsorption energy to be ag ood descriptor for the charget ransfer of intermediate products and discounts the volcanop lot relationship thati s widely used as ag uideline for tuning catalysts electivity.H ead-Gordon,B ell, and co-workers calculated single atoms (Cu, Ni, Pt, Pd, Cu, Rh, and Ir) added to gold and silver to converge on alloys containing Co, Rh, and Ir as particularly promisingc andidates for experimental verification. [58] 4.1. Compositional survey…”
Section: Co 2 !C 2 With Electrocatalytic Alloysmentioning
confidence: 99%
“…Thermodynamically,the selectivity is decided by the competitive adsorption of the two initial hydrogenation intermediates,C OOH* for the CO 2 RR, and H* for the HER. [18,19] Thestronger adsorption of COOH* will contribute to suppressing the HER since the active sites can be occupied by COOH* instead of H*. Forcases where the adsorption of H* is stronger,t he selectivity for carbonaceous products will be inhibited.…”
mentioning
confidence: 99%
“…Head‐Gordon et al., using DFT calculations, reported that single‐atom alloys, where isolated single‐atoms of Co, Rh, or Ir are located at the surface of Au or Ag, can be promising electrocatalysts for CO 2 reduction to C1 hydrocarbons, such as methane or methanol . The single‐atom alloys favored the formation of OHC* or HOC* over H*, suppressing H 2 production.…”
Section: Electrochemical Reactionsmentioning
confidence: 99%